2002
DOI: 10.1021/np0201063
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Diarylheptanoids from the Roots of Juglans mandshurica

Abstract: A new (2) and three known diarylheptanoids (1, 3, and 4), along with one known sesquiterpenoid (5), were isolated from the roots of Juglans mandshurica, and their structures were elucidated on the basis of spectroscopic studies. Four of these compounds (2-5) exhibited moderate cytotoxicities against human colon carcinoma and human lung carcinoma cell lines with IC(50)'s ranging from 2 to 25 microg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…3), thus the structure of 2 was established as (2S)-1,7-diphenyl-2-hydroxy-4E-hepten-3-one. The other fifteen known diarylheptanoids were also isolated from this plant and identified by comparing spectral data with those reported in literature; they were 3,6-furan-1,7-diphenylheptane (3) [8], 7-(4′′-hydroxy-3′′-methoxyphenyl)-1-phenyl-3,5-heptanediol (4) [9], (3R,5R)-1,7-diphenyl-3,5-heptanediol (5) [10], (5S)-5-hydroxy-7-(4′′-hydroxy-3′′-methoxyphenyl)-1-(4′-hydroxyphenyl)-3-heptanone (6) [6], (5S)-7-(4′′-hydroxy-3′′-methoxyphenyl)-1-(4′-hydroxyphenyl)-5-methoxy-3-heptanone (7) [6], (5S)-5-hydroxy-7-(4′′-hydroxyphenyl)-1-phenyl-3-heptanone (8) [9], (5S)-7-(4′′-hydroxyphenyl)-5-methoxy-1-phenyl-3-heptanone (9) [11], (5S)-1,7-diphenyl-5-methoxy-3-heptanone (10) [11], (5R)-5-hydroxy-7-(4′′-hydroxy-3′′-methoxyphenyl)-1-phenyl-3-heptanone (11) [12], (5R)-7-(4′′-hydroxy-3′′-methoxyphenyl)-5-methoxy-1-phenyl-3-heptanone (12) [13], (5R)-1,7-diphenyl-5-hydroxy-3-heptanone (13) [12], 7-( 4 ′ ′-hydroxy-3′′-methoxyphenyl)-1-phenyl-4E-hepten-3-one (14) [12], 7-(4′′-hydroxyphenyl)-1-phenyl-4E-hepten-3-one (15) [14], 1,7-diphenyl-4E-hepten-3-one (16) [13] and 7-(4′′-hydroxy-3′′-methoxyphenyl)-1-(4′-hydroxyphenyl)-4E-hepten-3-one (17) [14]. Compound 3 is a new natural product isolated from plants for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…3), thus the structure of 2 was established as (2S)-1,7-diphenyl-2-hydroxy-4E-hepten-3-one. The other fifteen known diarylheptanoids were also isolated from this plant and identified by comparing spectral data with those reported in literature; they were 3,6-furan-1,7-diphenylheptane (3) [8], 7-(4′′-hydroxy-3′′-methoxyphenyl)-1-phenyl-3,5-heptanediol (4) [9], (3R,5R)-1,7-diphenyl-3,5-heptanediol (5) [10], (5S)-5-hydroxy-7-(4′′-hydroxy-3′′-methoxyphenyl)-1-(4′-hydroxyphenyl)-3-heptanone (6) [6], (5S)-7-(4′′-hydroxy-3′′-methoxyphenyl)-1-(4′-hydroxyphenyl)-5-methoxy-3-heptanone (7) [6], (5S)-5-hydroxy-7-(4′′-hydroxyphenyl)-1-phenyl-3-heptanone (8) [9], (5S)-7-(4′′-hydroxyphenyl)-5-methoxy-1-phenyl-3-heptanone (9) [11], (5S)-1,7-diphenyl-5-methoxy-3-heptanone (10) [11], (5R)-5-hydroxy-7-(4′′-hydroxy-3′′-methoxyphenyl)-1-phenyl-3-heptanone (11) [12], (5R)-7-(4′′-hydroxy-3′′-methoxyphenyl)-5-methoxy-1-phenyl-3-heptanone (12) [13], (5R)-1,7-diphenyl-5-hydroxy-3-heptanone (13) [12], 7-( 4 ′ ′-hydroxy-3′′-methoxyphenyl)-1-phenyl-4E-hepten-3-one (14) [12], 7-(4′′-hydroxyphenyl)-1-phenyl-4E-hepten-3-one (15) [14], 1,7-diphenyl-4E-hepten-3-one (16) [13] and 7-(4′′-hydroxy-3′′-methoxyphenyl)-1-(4′-hydroxyphenyl)-4E-hepten-3-one (17) [14]. Compound 3 is a new natural product isolated from plants for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a number of natural compounds, such as phenolics, naphthoquinones, tetralones, flavonoids, naphthalenyl glucosides, diarylheptanoid and galloyl glycosides, have been isolated from Juglans species [1,2]. These compounds show several biological activities including cytotoxicity, anti-oxidation, inhibition of topoisomerase I and II, ribonuclease H, HIV-1 reverse transcriptase and pancreatic lipase as well as anti-complement activity [2][3][4][5][6][7][8]. In our previous study, 38 chemicals were extracted from J. mandshurica, including one newly discovered anthracene derivative, two new anthraquinones, and one new naturally occurring anthraquinone compound (Juglanthraquinone C, JC) that has shown strong cytotoxicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that these constituents exhibited inhibitory effects on DNA polymerase and RNase H activity, 8,10) as well as cytotoxic, 5,8,9) anti-HIV-1, 11) and anti-complement activities. 12) In this study, two galloyl monosaccharides, 1,2,6-trigalloyl glucose (1) and 1,2,3,6-tetragalloyl glucose (2), isolated from J. mandshurica were examined for their scavenging activities against some free y To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…3) A number of natural phenolics, naphthoquinones, naphthalenyl glucosides, tetralones, [5][6][7][8] diarylheptanoids, 5,[7][8][9] galloyl monosaccharides, and flavonoids 5,10) have previously been isolated from this plant. It has also been shown that these constituents exhibited inhibitory effects on DNA polymerase and RNase H activity, 8,10) as well as cytotoxic, 5,8,9) anti-HIV-1, 11) and anti-complement activities.…”
mentioning
confidence: 99%